Diarylmethyl Ethers for the Protection of Polyols - Sigthor Petursson (Journal of Chemistry)
The paper discusses the use of diarylmethyl ethers for the protection of hydroxyl groups, in particular, carbohydrate hydroxyl groups. The formation of these ethers can be done nonselectively by the thermal reactions of diryldiazomethanes via a carbene mechanism or by tin(II) halide catalysis of the diazo compounds with diols. The catalyzed reactions give useful regioselectivities.